Mindfulness: a tool for improving student well-being - Dictamen, Mayre (Conexiones UG, 2024)
The research was developed with the aim of understanding the utility of the mindfulness technique in the context as a tool to increase the psycho-emotional well-being of university students, given that currently, most students focus on meeting academic, social and family demands, forgetting to take care of and maintain good mental health and decreasing their levels of well-being. which generates a decompensation by not knowing themselves, nor developing their skills and levels of emotional tolerance. For this reason, it is proposed to study the beneﬁts of the practice of mindfulness in improving and maintaining their levels of well-being in university students, in order to understand the student in an integral way, through documentary research.
Keywords: Mindfulness; psychological well-being; students; mental health; university students